Pengaruh Corporate Social Responsibility (CSR) Terhadap Agresivitas Pajak: Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2017 - Nurcahyono Nurcahyono; Ida Kristiana (Universitas Muhammadiyah Semarang, 2019)
This study aims to examine the effect of Corporate Social Responsibility (CSR) on tax aggressiveness. This research was conducted at mining companies listed on the Indonesia Stock Exchange in 2017 and the sample in this study amounted to 41 companies. Measurement of the CSR variable using dammy and based on the GRI 4.0 index, tax aggressiveness is measured by the Effective Tax Rate. The research method used in this study is multiple linear regression. The results of this study show that corporate social responsibility has a negative effect on tax aggressiveness.